1987
DOI: 10.1111/j.1600-065x.1987.tb00500.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Ion Fluxes during Activation of Human T Lymphocytes: Role of Ca2+, Na+/H+ Exchange and Phospholipid Turnover

Abstract: The importance of increases in [Ca2+]i, stimulation of Na+/H+ exchange, and turnover of membrane phospholipids as signals for mitogen-induced activation of human T cells has been reviewed. In the presence of optimal concentrations of lectin and appropriately presented antigen, T cells increase [Ca2+]i, secrete IL2, express IL2 receptors and later divide. An increase in [Ca2+]i is critical for IL2 secretion in contrast to the requirements for IL2 receptor expression and IL2-IL2 receptor interaction. Treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
1

Year Published

1988
1988
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(70 citation statements)
references
References 76 publications
5
64
0
1
Order By: Relevance
“…The identification of such putative elements is currently ongoing. Since TPA induces proliferation in lymphoid cells (13) and in the BCBL-1 cell line induces cellular as well as KSHV replication, we conclude that in this cell type the LANAp promoter is not cell cycle regulated.…”
Section: Discussionmentioning
confidence: 77%
“…The identification of such putative elements is currently ongoing. Since TPA induces proliferation in lymphoid cells (13) and in the BCBL-1 cell line induces cellular as well as KSHV replication, we conclude that in this cell type the LANAp promoter is not cell cycle regulated.…”
Section: Discussionmentioning
confidence: 77%
“…Because all of these signaling pathways are upregulated via TCR activation, we believe that the above-mentioned studies support our conclusion of suppressed TCR-dependent pathways. In addition, Gelfand et al (13) reported that intracellular Ca 2ϩ release is critical for IL-2 secretion and cell proliferation of human T lymphocytes. This report also supports our conclusion that lidocaine inhibits IL-2 secretion and splenocyte proliferation via suppression of TCR activation and the downstream effects of this receptor.…”
Section: Discussionmentioning
confidence: 99%
“…2b) and the sustained plateau is prevented by EGTA which chelates extracellular Ca ~+ (Fig. 2 c) (Alcover et al, 1987;Finkel et al, 1987;Gelfand et al, 1987).…”
Section: The Effect Of Ca 2+ Chelators On Intracellular Ca 2+ Levelsmentioning
confidence: 95%
“…Ionomycin enhances both the release of Ca 2÷ from intracellular stores and the influx of Ca 2÷ from the extracellular environment (Clevers et al, 1988;Gardner, 1989;Gelfand et al, 1987). Thus a pathway that enhances the free Ca 2÷ concentration within the cell may create conditions unfavourable for virus expression.…”
Section: Introductionmentioning
confidence: 99%